The descriptive analysis of depressive symptoms and White Blood Cell (WBC) count between the sexual minorities and heterosexual identifying individuals in a nationally representative sample: 2005-2014 - Junjie Lu; Jiarui Yang; Jingyang Liang; David Mischoulon; Maren Nyer (BMC, 2023)
Abstract Background Sexual minorities are at a higher risk of suffering from depressive symptoms compared with heterosexual individuals. Only a few studies have examined the conditions of having depressive symptoms within different sexual minority groups, especially people with sexual orientation uncertainty in a nationally representative sample. Furthermore, few studies have explored whether the mean white blood count (WBC) is different between people with and without depressive symptoms among different sexual minority groups in a nationally representative sample. Methods We analyzed the National Health and Nutrition Examination Survey (NHANES) data from 2005 to 2014 with a sample of 14,090 subjects. We compared the prevalence of depressive symptoms in subpopulations stratified by sex, sexual minority status, and race. We also examined the difference in mean WBC count between depressed and non-depressed people among heterosexual individuals and different sexual minority groups. Additionally, two multivariable logistic regression models were used to explore the association between sexual minority status and depressive symptoms, treating sexual minority status as both a binary and categorical variable. Results Female sex (OR: 1.96, 95% CI: 1.72-2.22) and sexual minority status (OR: 1.79, 95% CI: 1.47-2.17) were both independently associated with depressive symptoms. Within the sexual minority population, subjects who were unsure about their sexual identities had the highest odds of having depressive symptoms (OR: 2.56, 95% CI: 1.40-4.68). In the subgroup analysis considering intersectionality, black sexual minority females had the highest rate of depressive symptoms (19.4%, 95% CI: 7.72-40.98). Finally, the mean WBC count differed significantly between people with and without depressive symptoms among male heterosexual individuals, female heterosexual individuals, and female sexual minorities, but not among male sexual minorities. Conclusions Based on sex, race, and sexual minority status, black females of sexual minority status had the highest rate of depressive symptoms. Within sexual minority groups, participants who were unsure about their sexual identities had the highest odds of having depressive symptoms. Finally, the mean WBC count was significantly higher among people with depressive symptoms than those without depressive symptoms only among male heterosexuals, female heterosexuals, and female sexual minorities, but not among male sexual minorities. Future research should investigate the social and biological mechanisms of the differences.